2020
DOI: 10.33151/ajp.17.809
|View full text |Cite
|
Sign up to set email alerts
|

Responding to a Cardiac Arrest: Keeping Paramedics Safe during the Covid-19 Pandemic

Abstract: This commentary aims to provide an overview of the current state and territory ambulance service cardiac arrest management recommendations to paramedics during the COVID-19 pandemic and highlight relevant risks to personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…• EMS calls during COVID-19, 7,8,10-19 • Reduced EMS operator response time, 7 • Ambulance response delays, 14,20,21 • Collateral mortality and morbidity among non-COVID-19 cases, 14,17,19,[22][23][24][25][26][27][28][29]31 and • Total ambulance call time. 17,29,[33][34][35]…”
Section: Charting the Data And Synthesizing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• EMS calls during COVID-19, 7,8,10-19 • Reduced EMS operator response time, 7 • Ambulance response delays, 14,20,21 • Collateral mortality and morbidity among non-COVID-19 cases, 14,17,19,[22][23][24][25][26][27][28][29]31 and • Total ambulance call time. 17,29,[33][34][35]…”
Section: Charting the Data And Synthesizing Resultsmentioning
confidence: 99%
“…The new regulations force the donning of appropriate PPE by EMS personnel in preparing for EMS calls, which is considered a time-consuming procedure that impacts the RT of ambulances. [33][34][35] Therefore, responding to highacuity trauma patients can be delayed by suiting up with PPE. Paradoxically, a scarcity of PPE and appropriate face masks is found to be a reason in some areas of the world to cause ambulance delays.…”
Section: Total Ambulance Call Timementioning
confidence: 99%
“…There are very few studies in the literature on the anxiety caused by COVID-19 and its effects on working life, such as its effect on productivity and efficiency. It is seen that the studies conducted are generally specific to the health sector (Hoşgör, Ülker Dörttepe and Sağcan, 2020;Lerner, Newgard and Mann, 2020;Whitfield, MacQuarrie and Boyle, 2020). However, no studies have been found in the literature in which the variables studied in this study are considered together.…”
Section: Tartışma Ve Sonuçmentioning
confidence: 99%
“…Literatürde COVID-19'un neden olduğu kaygı ve bunun üretkenliğe ve verimliliğe etkisi gibi çalışma yaşamına etkileri üzerine yapılmış çok az sayıda çalışma bulunmaktadır. Yapılan çalışmaların ise genellikle sağlık sektörü özelinde olduğu görülmektedir (Hoşgör, Ülker Dörttepe ve Sağcan, 2020;Lerner, Newgard ve Mann, 2020;Whitfield, MacQuarrie ve Boyle, 2020). Bununla birlikte literatürde, bu çalışmada incelenen değişkenlerin bir arada ele alındığı herhangi bir çalışmaya rastlanmamıştır.…”
Section: The Mediating Role Of Presenteeism In the Effect Of Employee Coronavirus Anxiety Levels On Productivity At Workunclassified
“…They also provide supportive and continuous health services in emergencies such as natural disasters and epidemics. If emergency health care personnel are to provide timely and effective health service to individuals in need of health care, it is necessary to meet their social, psychological, financial and moral needs and to provide them with support (Whitfield et al, 2020). It is obvious that they need such support more in extraordinary situations such as pandemics and disasters.…”
Section: Literature Reviewmentioning
confidence: 99%